Answer:
3x - y + 5 = 0
Explanation:
When two points are given and the equation of the line passing through those points are asked we use two - point form to determine the equation of the line.
Two - point form:
![$ (y - y_1)/(y_2 - y_1) = (x - x_1)/(x_2 -x_1) $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/sbesh4kstdswyfqy3izfz3ra3fcmf2o59l.png)
Here the two points are: (2,11) & (-8,-19).
Let
and
![$ (x_2, y_2) = (-8,-19) $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zi8cgf5si6bd8yyl474mdaw8geuex5zdvw.png)
Substituting in the formula we have:
![$ (y - 11)/(-19 - 11) = (x - 2)/(-8 - 2) $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mbzrul1l9rq6osq0gil9tysjer0jrfvnxa.png)
![$ \implies (y - 11)/(-30) = (x - 2)/(-10) $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/x1s9j5t8jf8y7xmq1t5o82ujrdog63t62k.png)
Simplifying we get:
y - 11 = 3x - 6
⇒ 3x - y + 5 = 0